Yitzhak Rabin : a political biography - Derfler, Leslie; SpringerLink (Online service). (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
A political and analytical biography, this book examines Yizhak Rabin's longtime leadership of the military and his political direction of the Jewish state, as well as his efforts to secure a peace with Egypt and with the Palestinians.
Keywords: Political science; Ethnology -- Middle East; Middle East -- History; Military history; World politics; Middle East -- Politics and government; International relations